People's Republic of China-Hong Kong Special Administrative Region : 2022 Article IV Consultation Discussions-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
Hong Kong SAR's economy is recovering strongly as ample policy space has allowed the enaction of swift and bold policy responses to address the unprecedented crisis emanating from multiple shocks, including notably the pandemic. But the recovery remains uneven, with private consumption lagging, owing, in part, to a zero- COVID tolerance approach. The financial sector has remained resilient supported by significant buffers, strong institutional frameworks, and a well-functioning Linked Exchange Rate System (LERS). Increasing financial linkages with Mainland China bring both opportunities and challenges for growth and financial stability.